Effect of organic ,chemicalfertilization and whey and on vegetative groweth of potatoes cv desiree - Al-Mohammedi, Omar H.; AL-Sahaf, Fadhil H.; Ati, Alaa S. (Journal of Kerbala for Agricultural Sciences, 2013)
An experiment was carried out in the experimental field of Horticulture Dept., College of Agriculture, University of Baghdad for two seasons (spring 2007 and 2008)to produce potato by organic fertilization. In spring 2007 season, class A seed tubers while in spring 2008 season, class Elite of the cv. Desiree potato was used. Two experiment were designed, first was the use of three sources of organic fertilizers (Poultry, three levels of cattle and sheep manure)in addition to conventional mineral fertilizer and no fertilization (control) treatment. In second experiment, cattle manure fertilizer in addition to whey were used. Results could be summarized as follows: Soil added of 10% poultry manures hasten the field emergence and was 26.21 and 27.14 days. Cattle manure at 15% with whey had the lowest number of days for field emergence in both seasons (28.97 and 29.68 days respectively). Manure treatment regardless the source and cattle manure 15% +whey all caused 100% emergence for both seasons Greatest number of stems was found when 10% poultry manure was added (4.60 and 4.52 stem/plant) and 15%cattle manure with whey was added (4.44 and 4.36 stem/plant)for the two seasons respectively ).Total leaf area on the other hand was found in mineral fertilized plants for both seasons (34.30 and 33.30 dm 2/plant respectively ).Greatest dry matter percentage was found with 10% poultry manure treatment (56.29 and 55.27 g/plant)and with 15% cattle manure and whey treatment (56.20and 55.16 g/ plant) for the two seasons respectively.